Telaah Filosofis terhadap Tapa Brata: Praktik Spiritual Menanggulangi Kecemasan dalam Pandemi Covid-19 - Suryosumunar, John Abraham Ziswan (Paradigma: Jurnal Kajian Budaya, 2021)
The COVID-19 pandemic, which is a global disaster, has an impact on all aspects of human life. Indonesia is one of the countries that have a high rate of COVID-19 incidences, which naturally has led to various policies intended to suppress further transmission by limiting social mobility. During this pandemic, people are faced with uncertain conditions that result in an increasing level of boredom, fear, and even public anxiety. The author was interested in exploring the realities of the COVID-19 pandemic by examining the possible relationship between public anxiety during the COVID-19 pandemic and an awareness of the need for spirituality which may be achieved by means of performing a Javanese spiritual practice called tapa brata. This practice was then examined in relation to public anxiety that occurred during the COVID-19 pandemic. Our analysis has generated several main results. Firstly, anxiety among the people during the pandemic is caused by a common awareness of the uncertain and constantly changing reality. Secondly, tapa brata is a mental practice of forming a calmer and wiser self which can adapt to all changes. Thirdly, tapa brata is an esoteric, personal practice that can overcome public anxiety during a pandemic and has a positive physiological effect on people’s immunity during the COVID-19 pandemic.